**Question:**f(x)=(x+4)/(x+2)

**Answers:**

f(x) = (x+4) / (x+2)

f(2) = (2+4) / (2+2) = 6/4 = 3/2, So...

[f(x) - f(2)] / (x-2)

= { [ (x+4) / (x+2) ] - 3/2 } / (x - 2)

= { [ 2(x+4) - 3(x+2) ] / [2(x+2)] } * [ 1 / (x - 2)]

= [ 2(x+4) - 3(x+2) ] / [2(x+2)(x-2)]

= (2x + 8 - 3x - 6) / [2(x+2)(x-2)]

= (-x + 2) / [2(x+2)(x-2)]

= - (x - 2) / [2(x+2)(x-2)]

The (x - 2) in the numerator cancels out with the (x - 2) in the denominator, so you get:

= -1 / [2(x+2)]

= -1 / (2x + 4)

Therefore, [f(x) - f(2)] / (x-2) = -1 / (2x + 4)

Next time post a question like this in the "Mathematics" category. It's a sub-category of the "Science & Mathematics" category. You're going to get a response much quicker that way...in fact, you're more likely to get a response if you do.

This article contents is post by this website user, EduQnA.com doesn't promise its accuracy.

**More Questions & Answers...**